PENGARUH LIKUIDITAS, LEVERAGE, PROFITABILITAS TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR DI BEI (Studi Kasus Pada Perusahaan Manufaktur Di Bursa Efek Indonesia 2009 â 2011) - Nugraha Ade Putra, 08.05.51.0149 (Students Journal of Economic and Management, 2014)
This study aims to examine and analyze the effect of liquidity, leverage and profitability on stock returns. sample of 30 manufacturing companies using purposave sampling method. The data obtained were then tested using regresion data program. The results show the validity of the data and fit, making it feasible to do the next test, the regression test, test and test hypotheses determination.Multiple linear regression test results revealed Stock Return = -0.031 + 0.787 (Liquidity) - 0.018 (Leverage) - 0.036 (Profitability), with the results it can be seen that the liquidity variables significantly positive effect on stock returns while the variable leverage and profitability has a negative effect not significant impact on stock returns. Figures obtained from the test of determination Adjusted R square of 0.180, which indicates that the three independent variables explain the dependent variable and the remaining 18% is explained by other factors beyond research. To test the hypothesis used the t test and F test From the t-test can be proved that the liquidity variable positive and significant impact on stock returns this is indicated by the value of t is greater than t table. Keywords: Liquidity , Leverage , Profitability , Stock Returns.